Outcomes of adjunctive steroid therapy in adult patients with bacterial meningitis in Taiwan: A nationwide population-based epidemiologic study. (March 2019) - Lai, Yun-Ru; Lin, Jr-Rung; Chang, Wen-Neng; Tsai, Nai-Wen; Huang, Chih-Cheng; Wang, Hung-Chen; Su, Yu-Jih; Lin, Wei-Che; Cheng, Ben-Chung; Su, Chih-Min; Hsiao, Sheng-Yuan; Kuo, Chun-En; et al.
Highlights: Case-fatality rates were 11.5% in the placebo group and 19.9% in the steroid groups. Steroid group had a more fulminant clinical course and unfavorable outcomes. The length of hospital stay is higher in steroid group. Medical costs of hospitalization is higher in steroid group. Abstract: Background: Although corticosteroids are an effective anti-inflammatory adjuvant therapy, the role of adjunctive steroid therapy in treating adult bacterial meningitis in Taiwan remains controversial. Methods: Cases of acute bacterial meningitis were identified from the annual hospitalization discharge claims of the National Health Insurance Research Database using International Classification of Diseases, Ninth Revision codes from January 2000 to December 2013. Patients were classified into two groups: (1) steroid group (adjunctive steroids and empirical antibiotics) and (2) placebo group (empirical antibiotics only). Results: There were 15, 037 patients enrolled in this study; of these, 57% (7175/15, 037) and 52% (7862/15, 037) were placed in the placebo and steroid groups, respectively. The case-fatality rates were 11.5% (826/7175) in the placebo group and 19.9% (1562/7862) in the steroid groups during hospitalization (P = 0.77). Further, the hazard ratio (relative to placebo group) of in-hospital and one-year case fatality rate were 0.923 (95% confidence interval [CI]: 0.846–1.007, P = 0.073) and 1.514 (95% CI: 1.425–1.608, P < 0.0001) according to the multivariate Cox model after adjustment for age and sex. Conclusion: On the basis of these results, steroid group had a more fulminant clinical course (e.g., acute respiratory failure and pneumonia, etc.), and unfavorable outcomes than placebo group. Therefore, more prospective, randomized, double-blind trials are warranted to evaluate the efficacy of adjunctive steroid therapy in treating adult bacterial meningitis in Taiwan.